Dietary sunflower oil modulates milk fatty acid composition without major changes in adipose and mammary tissue fatty acid profile or related gene mRNA abundance in sheep. (2nd December 2014) - Castro-Carrera, T.; Frutos, P.; Leroux, C.; Chilliard, Y.; Hervás, G.; Belenguer, A.; Bernard, L.; Toral, P. G.
Abstract : There are very few studies in ruminants characterizing mammary and adipose tissue (AT) expression of genes and gene networks for diets causing variations in milk fatty acid (FA) composition without altering milk fat secretion, and even less complementing this information with data on tissue FA profiles. This work was conducted in sheep in order to investigate the response of the mammary gland and the subcutaneous and perirenal AT, in terms of FA profile and mRNA abundance of genes involved in lipid metabolism, to a diet known to modify milk FA composition. Ten lactating Assaf ewes were randomly assigned to two treatments consisting of a total mixed ration based on alfalfa hay and a concentrate (60 : 40) supplemented with 0 (control diet) or 25 (SO diet) g of sunflower oil/kg of diet dry matter for 7 weeks. Milk composition, including FA profile, was analysed after 48 days on treatments. On day 49, the animals were euthanized and tissue samples were collected to analyse FA and mRNA abundance of 16 candidate genes. Feeding SO did not affect animal performance but modified milk FA composition. Major changes included decreases in the concentration of FA derived from de novo synthesis (e.g. 12:0, 14:0 and 16:0) and increases in that of long-chain FA (e.g. 18:0, c 9-18:1, trans -18:1 isomers and c 9, t 11-CLA); however, they were not accompanied by significant variations in the mRNA abundance of the studied lipogenic genes (i.e. ACACA, FASN, LPL, CD36, FABP3, SCD1 and SCD5 ) and transcription factors ( SREBF1 and PPARG ), or in the constituent FA of mammary tissue. Regarding the FA composition of AT, the little influence of SO did not appear to be linked to changes in gene mRNA abundance (decreases of GPAM and SREBF1 in both tissues, and of PPARG in the subcutaneous depot). Similarly, the great variation between AT (higher contents of saturated FA and trans -18:1 isomers in the perirenal, and of cis -18:1, c 9, t 11-CLA and n-3 PUFA in the subcutaneous AT) could not be related to differences in gene mRNA abundance due to tissue site (higher LPL and CD36, and lower SREBF1 in perirenal than in subcutaneous AT). Overall, these results suggest a marginal contribution of gene expression to the nutritional regulation of lipid metabolism in these tissues, at least with the examined diets and after 7 weeks on treatments. It cannot be ruled out, however, that the response to SO is mediated by other genes or post-transcriptional mechanisms.